Growth hormone supplementation ameliorates blastocyst euploidy rates and improves pregnancy outcomes in women undergoing preimplantation genetic testing for aneuploidy cycles - Guo, Qingqing; Liu, Peihao; Zhou, Wei; Xia, Mingdi; Li, Jing; Lu, Juanjuan; Ma, Jin-Long; Chen, Zi-Jiang; Yan, Junhao (Frontiers in Endocrinology, 2023)
Growth hormone (GH) supplementation has been shown to improve oocyte quality and live birth, but few studies have examined whether GH can reduce embryonic aneuploidy. Chromosomal abnormalities in preimplantation embryos have been regarded as the principal cause of implantation failure and miscarriage, and an increased percentage of aneuploid embryos has been observed in patient cohorts with unexplained recurrent pregnancy loss (RPL), recurrent implantation failure (RIF), and advanced maternal age. This prospective cohort study focused on these women whose previous PGT-A cycle ended up with no transferrable blastocysts, or the aneuploidy rate was above 50% and no live birth was acquired. 208 women were recruited in the study, and the participants were divided into GH co-treatment and comparison groups (GH co-treatment group: 96 women, comparison group: 112 women) according to whether GH co-treatment was implemented in the next PGT-A cycle. In addition, within the GH co-treatment group, the previous failed cycle constituted the self-control group. Compared to the self-control and comparison groups, the rate of euploid blastocysts was significantly higher in the GH co-treatment group (GH vs self-control: 32.00% vs 9.14%, odds ratio [OR]: 4.765, 95% confidence interval [CI]: 2.420–9.385, P < 0.01; GH vs control: 32.00% vs. 21.05%, OR: 1.930, 95% CI: 1.106–3.366, P = 0.021), and their frozen embryo transfers resulted in more pregnancies and live births. In the subgroup analysis, for the <35 and 35-40 years groups, the euploidy rate in the GH co-treatment group was significantly higher than those in the self-control and comparison groups, but in the >40 years group, there was no difference in euploidy rate. Our study presents preliminary evidence that GH supplementation may ameliorate blastocyst aneuploidy and improve pregnancy outcomes in women who have previously experienced pregnancy failures along with high aneuploidy rates, particularly in those younger than 40 years. Therefore, the use of GH in such women should be considered. However, considering the limited sample size and mixed indications for PGT-A, further scientific research on the underlying mechanism as well as clinical trials with larger sample sizes are needed to confirm the effects and optimal protocols.